2023
DOI: 10.1002/ppp3.10360
|View full text |Cite
|
Sign up to set email alerts
|

The Red List for the endemic trees of Colombia: Effective conservation targeted for plants required in biodiversity hotspots

Abstract: Conserving trees is fundamental to maintaining forests, which are home to about half of the global biodiversity and provide unmeasurable benefits to people. Colombia has 5868 known species of trees, 1148 of which are endemic to the country. Unfortunately, 45% of the endemic trees of Colombia are threatened with extinction, and therefore, the ecosystem services they provide might be in jeopardy. This study represents an important contribution to conservation planning for the endemic trees of a megadiverse count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When focusing on endemic species, the situation is critical in both Colombia and Ecuador. The 83% (36/43) of endemic palms are potentially threatened in the Chocó and Andes of Colombia (Table 2) which is much higher than the 45% of all Colombian endemic tree species assessed as threatened (Lopez‐Gallego & Morales‐Morales, 2023). This level of threat is equivalent to those reported for Madagascar where 86% of the mostly endemic species were assessed as threatened (Rakotoarinivo et al, 2014, 2020) and close to the 78% of endemic plants assessed as threatened in Ecuador in general (León‐Yánez et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…When focusing on endemic species, the situation is critical in both Colombia and Ecuador. The 83% (36/43) of endemic palms are potentially threatened in the Chocó and Andes of Colombia (Table 2) which is much higher than the 45% of all Colombian endemic tree species assessed as threatened (Lopez‐Gallego & Morales‐Morales, 2023). This level of threat is equivalent to those reported for Madagascar where 86% of the mostly endemic species were assessed as threatened (Rakotoarinivo et al, 2014, 2020) and close to the 78% of endemic plants assessed as threatened in Ecuador in general (León‐Yánez et al, 2011).…”
Section: Discussionmentioning
confidence: 94%
“…When focusing on endemic species, the situation is critical in both Colombia and Ecuador. The 83% (36/43) of endemic palms are potentially threatened in the Choc o and Andes of Colombia (Table 2) which is much higher than the 45% of all Colombian endemic tree species assessed as threatened (Lopez-Gallego & Morales-Morales, 2023).…”
Section: Conservation Of Palmsmentioning
confidence: 92%
“…One possible alternative explanation for the positive relationship between number of local common names and national vulnerability status may be that most of the documented plants are regional, and so may be so widespread that the species is considered of little conservation concern or not yet in need of evaluation. Lopez-Gallego & Morales-Morales (2023) found that endemic and threatened species of trees were not uniformly distributed across the biographical regions of Colombia, and for trees in the Amazonia and Guyana shield regions, most species were labeled as Least Concern by the IUCN, because of large extant of occurrence (EOO)—the estimated minimum convex polygon that encompasses all known occurrences of a species—and lack of threats (Lopez-Gallego & Morales-Morales, 2023). The plant species included in this study may also have been assessed as Least Concern for these reasons.…”
Section: Discussionmentioning
confidence: 99%
“…In species rich countries, like Colombia (Lopez‐Gallego & Morales‐Morales, 2023), effective approaches are needed to provide rigorous methods to rapidly assess the threat status of trees in large diverse countries. These assessment efforts are still hampered by the substantial fraction of poorly known species, or even undiscovered species, in some of the world's most biodiverse countries.…”
Section: Managing Limits To Knowledgementioning
confidence: 99%